Assessment of Fermented Corn Mixed with Fish Meal as a Chicken Additive for Healthy Broiler Chicks - Iheukwumere, I. H.; Iheukwumere, C. M.; Idigo, M. A.; Ezekwueche, S. N. (Journal of Agriculture, Food Technology and Sustainability, 2025)
Poultry production is one of the fastest-growing sectors in global agriculture, providing a major source of animal protein through meat and eggs. This study was undertaken to evaluate the effect of fermented corn chaff mixed with fish meal as a chicken additive for healthy broiler chicks. The effects of the fermented feeds on the broiler chicks were determined using in vivo techniques. The fermenter used in the study was identified to be Lactobacillus acidophilus strain DSN20079 (LADSM). The study revealed that there was a significant (P<0.05) increase in the body weight of the test chicks fed with the mixed fermented feed starting from week 1 (172 g) down to week 6 (1784 g). There was also an increase in the organ weights of the chicks (liver, kidney, lungs and heart). The feed conversion ratio (FCR) showed that in week 1, the FCR group of the test group (2.471) was higher than the control group, and during weeks 2,3 and 4, the FCR of the control group was higher than the test group, but during weeks 5 and 6, the FCR of the test group was higher than the control group. The blood indices of the test chicks revealed that there was an increase in the counts of WBC, RBC, PLT, monocyte, basophil and lymphocyte but a reduction in the number of neutrophil and eosinophil. Therefore, the study concluded that the fermented corn chaff mixed with fish meal exhibited pronounced activity on the growth performance of the chicks and could be used as an additive for healthy broiler chicks.